Clinically-Relevant ABC Transporter for Anti-Cancer Drug Resistance - Zheng, Yongcheng; Ma, Lingling; Sun, Qiu (Frontiers in Pharmacology, 2021)
Multiple drug resistance (MDR), referring to the resistance of cancer cells to a broad spectrum of structurally and mechanistically unrelated drugs across membranes, severely impairs the response to chemotherapy and leads to chemotherapy failure. Overexpression of ATP binding cassette (ABC) transporter is a major contributing factor resulting in MDR, which can recognize and mediate the efflux of diverse drugs from cancer cells, thereby decreasing intracellular drug concentration. Therefore, modulators of ABC transporter could be used in combination with standard chemotherapeutic anticancer drugs to augment the therapeutic efficacy. This review summarizes the recent advance of the important cancer-related ABC transporters, focusing on their physiological functions, structures and the development of new compounds as ABC transporter inhibitors.